Relationships between emotional intelligence, perceived and actual leadership effectiveness in the military context - Koh, Cheng Boon (2019)
Despite the importance of emotional intelligence and leadership effectiveness, few studies have been conducted in real-life contexts and few have distinguished between perceived and actual leadership effectiveness. This repeated measures study involving 86 officer cadets from the Republic of Singapore Air Force (RSAF) investigated these relationships in a military context. Quantitative data were collected from two self-report questionnaires: the Wong and Law Emotional Intelligence Scale and the Perceived Leadership Effectiveness Scale. These two self-report tools were also administered to the participants’ peers to examine the agreement between self and other assessments of emotional intelligence. A behavior-based leadership assessment rubric completed by the participants’ supervisors was used to determine actual leadership performance. Significant positive relationships were found between emotional intelligence and both perceived and actual leadership effectiveness, as assessed by peers and supervisors, respectively. This study contributes to the understanding of emotional intelligence as a global construct, and demonstrates that it is significantly associated with leadership effectiveness in a military training context. The findings have practical implications for using emotional intelligence to enhance leadership effectiveness.